Redox noninnocence in coordinated 2-(arylazo)pyridines: steric control of ligand-based redox processes in cobalt complexes. - Ghosh, P; Samanta, S; Roy, S; Joy, S; Krämer, T; McGrady, J; Goswami, S (2013)
A series of cobalt complexes of ligands based on the 2-(arylazo)pyridine architecture have been synthesized, and the precise structure and stoichiometry of the complexes depend critically on the identity of substituents in the 2, 4, and 6 positions of the phenyl ring. The 2-(arylazo)pyridine motif can support either Co(II) complexes with neutral ligands, Co(II)Cl2(L(a))2 (1), Co(II)Cl2(L(c))2 (3), [Co(II)Cl(L(b))2]2(PF6)2 (5[PF6]2), or Co(III) complexes of reduced 2-(arylazo)pyridine ligand radical anions, L(•-), Co(III)Cl(L(b•-))2 (2), Co(III)Cl(L(c•-))2 (4), and Co(III)Me(L(b•-))2 (6). All three members of the latter class are based on approximately trigonal-bipyramidal CoX(L(•-))2 architectures [L = 2-(arylazo)pyridine] with two azo nitrogen atoms and the X ligand (X = Cl or Me) in the equatorial plane and two pyridine nitrogen atoms occupying axial positions. Density functional theory suggests that the electronic structure of the Co(III) complexes is also dependent on the identity of X: the strong σ-donor methyl gives a low-spin (S = 0) configuration, while the σ/π-donor chloro gives an intermediate-spin (S = 1) local configuration. In certain cases, one-electron reduction of the Co(II)X2L2 complex leads to the formation of Co(III)X(L(•-))2; i.e., reduction of one ligand induces a further one-electron oxidation of the metal center with concomitant reduction of the second ligand.